ANALISIS LEVERAGE DAN PROFITABILITAS DALAM MEMPREDIKSI FINANCIAL DISTRESS STUDI EMPIRIS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Anneke Novia Anggraini; Arisyahidin Arisyahidin (Commodities, Journal of Economic and Business, 2020)
This study aims to examine the effect of leverage ratios measured using debt to total assets or debt ratios (DAR) and profitability ratios measured using return on assets (ROA) in predicting financial distress in food and beverage companies listed on the Stock Exchange Indonesia period. This research is a quantitative study, while the study population was taken from Food and Beverage companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The number of samples selected was 10 company samples determined by the purposive sampling method. This type of secondary data was obtained from www.idnfinancial.com. The data analysis method used is the Classic Assumption Test and Multiple Linear Regression Analysis using SPSS version 16. The results of the study show that: 1) the leverage ratio and profitability ratio together (simultaneously) influence in predicting financial distress. 2) Leverage Ratio (DAR) has an influence in predicting financial distress, t calculate 1,400 with a significance of 0.168 at a significance level of 20%. 3) Profitability Ratio (ROA) effect in predicting financial distress, t arithmetic - 3,003 with a significance of 0.04 level of 5%.